Diagnostic Error in Pediatric Cancer. (January 2018) - Carberry, Andrea R.; Hanson, Keith; Flannery, Ashley; Fischer, Megan; Gehlbach, Jonathan; Diamond, Carol; Wald, Ellen R.
The purpose of this study was to ( a ) determine the frequency of diagnostic errors in pediatric cancer, ( b ) categorize errors, and ( c ) underscore themes associated with misdiagnosis. This is a retrospective cohort study at a tertiary children's hospital of 265 patients with new oncologic diagnoses. The diagnostic error rate was 28%. Compared with those with no diagnostic error, those in whom there was an error were more likely to have ( a ) more visits before diagnosis ( P < .001), ( b ) not been seen in an acute care setting ( P = .03), ( c ) inappropriate treatment ( P < .001), and ( d ) misinterpreted laboratory studies or imaging ( P < .001). Themes in diagnostic errors were lack of appropriate evaluation for persistent symptoms (47%), failure to recognize signs and symptoms suggestive of malignancy (45%), and misinterpretation of tests (8%). Clinicians should consider diagnostic evaluation for multiple visits for the same complaint or a constellation of signs and symptoms suggestive of malignancy.